The Utilization of Rice Wastewater Combined With Red Dragon Fruit (Hylocereus polyrhizus) as Basic Ingredients of Nata De Leri - Meri Septiana; Suci Wulan Pawhestri; Nurhaida Widiani; Rina Budi (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2019)
Nata de leri is one of the products produced from fermented organic white, red, black rice washing water with the addition of red dragon fruit skin extract. In javanese the rice washing water is called Leri so that the resulting nata is called “Nata De Leri”. (carbohydrates, proteins, minerals) that are carried away from the rice membrane during the washing process. So that it can be utilized by microorganisms as a medium in making nata. The addition of red dragon fruit skin extract gives color because it contains a lot of anthocyanin and also the fiber and water content is very high. The purpose of this research was to determine the organoleptic and chemical characteristics of nata. This research used a qualitative descriptive method using a 2 factor complete randomized design and the treatment given was 75% of white, red, black rice washing water concentration, The concentration of red dragon fruit skin extract 75%, 50%, and 25%. The results showed that the most preferred texture on the addition of 75% red dragon fruit skin extract was an average of 4,65, the most preferred color in the addition of 75% and 25% red dragon fruit skin extract, the aroma of the average panelist doesn’t like all the aroma of nata de leri, for the taste all the samples were liked by the panelists because of their sweet taste. While the water content and crude fiber content produced are quite high on average but do not exceed SNI.